2016
DOI: 10.1002/2016jb013095
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc isotope systematics of altered oceanic crust at IODP Site 1256 in the eastern equatorial Pacific

Abstract: This paper presents the first combined Cu and Zn isotopic study of altered oceanic crust at Integrated Ocean Drilling Program (IODP) Hole 1256D that penetrates a volcanic section, a lava‐dyke transition zone, a sheeted dyke complex, and a plutonic complex. In the volcanic section, all but one rocks have Cu and Zn isotopic compositions similar to fresh mid‐ocean ridge basalt (MORB), reflecting restricted seawater circulation and low oxygen fugacity. Rocks in the transition zone have MORB‐like δ65Cu and δ66Zn, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 76 publications
(207 reference statements)
5
45
0
1
Order By: Relevance
“…Analyses of in‐house and international reference standards processed with the studied peridotites and pyroxenites yield δ 66 Zn = 0.28 ± 0.03‰ (2SD, n = 60) for IRMM3702, δ 66 Zn = 0.31 ± 0.05‰ (2SD, n = 6) for BHVO‐2, 0.22 ± 0.05‰ (2SD, n = 8) for JP‐1, and 0.26 ± 0.04‰ for DTS‐2 (2SD, n = 4) (Table ). These values agree well within error with previously published values (Chen et al, , ; Doucet et al, ; Huang et al, ; Huang, Chen, et al, ; Huang, Zhang, et al, ; Moynier et al, ; Sossi et al, ; Wang et al, ). This, combined with consistent results for repeated analyses (Table ), assures the accuracy and precision of our Zn isotopic data.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Analyses of in‐house and international reference standards processed with the studied peridotites and pyroxenites yield δ 66 Zn = 0.28 ± 0.03‰ (2SD, n = 60) for IRMM3702, δ 66 Zn = 0.31 ± 0.05‰ (2SD, n = 6) for BHVO‐2, 0.22 ± 0.05‰ (2SD, n = 8) for JP‐1, and 0.26 ± 0.04‰ for DTS‐2 (2SD, n = 4) (Table ). These values agree well within error with previously published values (Chen et al, , ; Doucet et al, ; Huang et al, ; Huang, Chen, et al, ; Huang, Zhang, et al, ; Moynier et al, ; Sossi et al, ; Wang et al, ). This, combined with consistent results for repeated analyses (Table ), assures the accuracy and precision of our Zn isotopic data.…”
Section: Methodssupporting
confidence: 92%
“…Nb/Nb* = Nb PM /(Th PM × La PM ) 0.5 , PM denotes primitive mantle normalization. Nb/Nb* and Sr isotopic data are taken from Hart et al (), and Zn isotopic data are taken from Huang et al () for altered lower (ALOC) and upper (AUOC) oceanic crust. Zinc isotopic data for deep‐sea sediments are taken from Maréchal et al (), Bentahila et al (), and Little et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 87/86 Sr AOC = 0.70458, Staudigel et al, 1995). Nonetheless, this process does not alter its Nd and Zn isotope composition ( 143/ 144 Nd AOC = 0.51308; δ 66 Zn AOC = +0.27 ± 0.01‰, Staudigel et al, 1995;Huang et al, 2016). Consequently, we argue that MORB-eclogite cannot account for the extreme Zn enrichment and global trends between Zn and Zn-Sr-Nd isotopes in oceanic basalts.…”
Section: Morb-type Oceanic Crust Recyclingmentioning
confidence: 72%
“…Recently Zn isotopes have been shown to be sensitive to mantle partial melting [ Doucet et al ., ; Wang et al ., ] and igneous differentiation [ Chen et al ., ], but owing to the complex metasomatic and metamorphic history of the studied samples, coupled with the lack of a comprehensive study of Zn isotopes in global MORB and oceanic gabbros, it is difficult to conclude if the variations in Zn isotope composition observed here reflect primary magmatic process or modification by late stage alteration and metasomatic processes. While it has previously been stated that the process of low‐temperature seafloor alteration of the upper, basaltic oceanic lithosphere has little effect on Zn isotopes, the same study demonstrated that high‐temperature (>350°C) hydrothermal circulation and complexing of light Zn isotopes in hydrothermal fluids could drive the Zn isotope composition toward heavier δ 66 Zn values in the gabbroic portion of the oceanic lithosphere [ Huang et al ., ]. This observation could be invoked to explain the range of δ 66 Zn values observed in the Zermatt and Queyras metagabbros, but as the samples now preserve a subduction‐related, Alpine overprint to their mineralogy it is not possible to unambiguously conclude on the effect of seafloor hydrothermal activity on the Zn isotope compositions of these rocks.…”
Section: Discussionmentioning
confidence: 99%